If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1 + x + 4 + 36 = 2x + 46 Reorder the terms: -1 + 4 + 36 + 2x + x = 2x + 46 Combine like terms: -1 + 4 = 3 3 + 36 + 2x + x = 2x + 46 Combine like terms: 3 + 36 = 39 39 + 2x + x = 2x + 46 Combine like terms: 2x + x = 3x 39 + 3x = 2x + 46 Reorder the terms: 39 + 3x = 46 + 2x Solving 39 + 3x = 46 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 39 + 3x + -2x = 46 + 2x + -2x Combine like terms: 3x + -2x = 1x 39 + 1x = 46 + 2x + -2x Combine like terms: 2x + -2x = 0 39 + 1x = 46 + 0 39 + 1x = 46 Add '-39' to each side of the equation. 39 + -39 + 1x = 46 + -39 Combine like terms: 39 + -39 = 0 0 + 1x = 46 + -39 1x = 46 + -39 Combine like terms: 46 + -39 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 3x+y=45 | | 8(2t-9)=-88 | | 2(f-10)=-34 | | -10(s+2)=-95 | | F(-4)=2x^/x-1 | | -2=-3(2x+4) | | 3(4x-1)=8 | | 3(4s+6)=174 | | ab+c=5solvec | | x^2+22x+115=0 | | 2n+4sobren+1n=2 | | 6(x+7)=-2(5-x) | | -2x=-2x+8 | | 4=4(5x-6) | | 4(2x+7)=9 | | =(2x-5)(3x+8)+7 | | 2n+4sobren+1=2 | | an=n/(n-1),n≥2 | | 14x+2=-2x | | 6/7=42 | | 5a^2+26a-63=0 | | 9x+16=4c | | 88/21=x | | 2200/525=x | | 2200/525 | | (3z/8)-7=-6 | | 11.6=1.5(x+0.15-3.5) | | 2+3yi=(x-1)+3i | | x/15=0.4 | | x/15=0.5 | | (x/7)-8=6 | | 10n^2+130n-10800=0 |